Building Qualitative Research Capacity Among Interdisciplinary Teams to Investigate Girls' Challenges With Menstruation: Process and Lessons Learned From a 14-Country E-Course. (December 2019) - Caruso, Bethany A.; Ellis, Anna; Sclar, Gloria; Girod, Candace; Penakalapati, Gauthami; Sahin, Murat; Cavill, Sue
Public health–related decisions are influenced by a variety of actors operating on local to global levels, including community leaders, educators, nongovernment organizations, government officials, donors, and researchers, many of whom may lack formal public health training. The provision of public health instruction to interdisciplinary professionals has the potential to strengthen the capacity of all stakeholders to make informed, evidenced-based decisions about health policies and programs. The use of online learning is emerging as a promising means of providing public health training, particularly among those living in geographically disparate areas and from multidisciplinary backgrounds. This article describes an online course created to teach participants in stakeholder teams from 14 low- and middle-income countries how to design and conduct qualitative research to understand girls' challenges managing menstruation at school. The goal of the course was to strengthen each country team's ability to conduct research by building the capacity of the members. Thus, completion of the course by all team members was an objective, but less of a focus than assuring that each team as a collective was gaining public health insights and working together to make informed decisions about their research goals. This course led to benefits beyond capacity strengthening, including the formation of a broader community of learning and practice that extended beyond country boundaries. We recommend embedding training opportunities for multidisciplinary stakeholders into research endeavors given the potential for positive effects on individual participants and overall policy decisions to improve community health and provide lessons learned for doing so.